ANALYSIS OF PENSTOCK DESIGN AND LOSSES USING DARCY-WEISBACH EQUATION IN A MICRO HYDRO POWER PLANT AT WISATA TELAGA RIVER, MALANG (Journal of Renewable Energy and Mechanics, 2025)
This study presents the design analysis and energy loss calculation of a penstock system for a micro hydro power plant at the Wisata Telaga River. The analysis includes the determination of pipe length using geometric estimation, selection of pipe diameter based on hydraulic parameters, and evaluation of energy losses using the Darcy-Weisbach equation. A 0.45 m HDPE pipe was selected, and a gross head of 9.35 m was considered. The calculated flow velocity was 2.67 m/s, yielding a major head loss of 0.19 m and a minor loss of 0.18 m. The effective head was 8.98 m, resulting in an estimated net power output of 31.22 kW with an efficiency of 96%. These findings demonstrate the technical feasibility and efficiency of the proposed penstock design for rural micro-hydro applications.